Idbview: a database and interactive platform for respiratory-associated disease - Peng, Bingming; Luo, Tingting; Fu, Xingmeng; Zhou, Yingzhen; Fu, Zhou; Wang, Ting (Frontiers in Immunology, 2024)
Public databases have become invaluable resources for disease research, particularly in the realm of identifying and validating biomarkers, thus playing a significant role in enhancing our understanding of respiratory diseases. To facilitate this understanding, the development of user-friendly analytical tools and advanced systematic models that leverage the growing omics data and clinical information datasets is essential. Despite the importance of such resources, the research progress related to respiratory diseases is hindered by the absence of a centralized platform housing easily accessible datasets and accompanying visualization tools. In an effort to streamline and standardize information sharing across diverse respiratory research initiatives, we introduce Idbview, a specialized digital database focusing on respiratory conditions, offering interactive visualization functionalities powered by both Vue and R Shiny applications. Idbview brings together clinical data and various omics datasets, serving as a centralized repository, while also providing users with a suite of interactive tools to analyze and visualize data from multiple perspectives. As a comprehensive resource hub, Idbview aims to support the research community in conducting further studies in both clinical and bioinformatics domains, with the website accessible at https://idbview.com.